Analyzing Students’ Self-Reflection on Project-Based Learning and Caption Text - Wida Widarni (Journal of English Education and Teaching, 2023)
This study used mixed methods and focused on discovering the students’ self-reflection on project-based learning implementation and their competence in writing caption text relating to using the present tense and interpreting visual aspects of it in the twelfth grade of science at SMA PGRI Cipanas. There were 35 students chosen as samples for the study. The data were collected through a questionnaire, an interview, and observation. The result of the questionnaire showed that their self-reflection got an average of 51.8% on pre-, 47.7% during, and 42.3% on post-implementation of PjBL in learning caption text. Meanwhile, based on the interview, students gave a good or positive reflection on PjBL implementation in learning caption text. Second, their self-reflection on their competence in writing the caption text showed that they delivered positive reflection and good development. The questionnaire and interview results demonstrated this: 61.4% on simple present tense forms, 56.5% on verbs, and 70.6% on time signals. Based on the scoring and classification of simple present tense and vocabulary, they got score of 5, or excellent. Meanwhile, based on the types of grammar, students’ simple present-tense sentences belong to descriptive grammar.